Guidebook 14. Field Trip Guidebook for the Precambrian Terrane of the Minnesota River Valley - Weiblen, Paul W. (Minnesota Geological Survey, 1982)
PREPARED FOR THE LUNAR AND PLANETARY INSTITUTE TOPICAL CONFERENCE ON PLANETARY VOLATILES, OCTOBER 9-12, 1982 The gently rolling farmland of southwestern Minnesota is a deceptive blanket over a rich record of the evolution of the earth's crust. The effects of Pleistocene glaciation dominate the area, and the landscape is characterized by a wide variety of glacial deposits which cover most of the bedrock geology. However, many outcrops are a product of glacial erosion and all the Precambrian outcrops in the Minnesota River Valley (MRV) were exposed by steambed erosion in the Glacial River Warren. This river drained Glacial Lake Agassiz prior to the disappearance of the ice sheet which prevented northward drainage to Hudson Bay. As can be seen in Figure 2, the Precambrian rocks of Minnesota occupy a central position in the North American continent. This position is reflected in the present day drainage pattern of the continent. Despite the low topographic relief (600-2,000 ft), there are three major drainage divides in Minnesota. The gentle relief and low elevation are also deceptive indicators of the crustal thickness of the North American continent in the region, which is on the order of 40 km. Despite its thickness and antiquity, the crust in Minnesota has remained geologically active. This is attested to in part by the fact that the Mesozoic north-south hinge line of the sedimentary basins involved in the formation of the Rocky Mountains crossed Minnesota. During the Paleozoic the region was involved in a number of oscillations of epicontinental seas. The distribution of the thin veneer of Phanerozoic rocks (maximum thickness less than 600 m), which were produced in these two episodes of crustal evolution, is shown in Figure 3 and in the geologic map of Minnesota on the frontispiece of the guidebook The geologic record is briefly outlined on the back cover. The thick, "stable" crust in the region is currently involved in the isostatic rebound associated with the disappearance of the Pleistocene ice sheets over North America. The locations of 12 recorded earthquakes in Minnesota are shown on Figure 3. The distribution of the earthquakes appears to be related to Precambrian tectonic features (Mooney and Morey, 1981), and may be related to reactivation of old fault systems in the course of isostatic rebound (Dutch, 1981). The Precambrian rocks in Minnesota define five distinct geologic terranes. The geology of these terranes is briefly outlined on the last page of the guidebook, and further details may be found in Sims and Morey ( 1972) and in more recent papers listed in Morey and others (1981). The outcrops in the MRV are part of the oldest terrane (I). They contain a record of a broad spectrum of igneous and metamorphic rocks which span a time interval from at least 3,500 to 1,800 m.y. Terrane I extends into central Minnesota where it is separated from the greenstone-granite terrane (II) to the north by a complex tectonic zone.